Bacillus isolates VTGP. A-D. 30808 Alcaligenes sp., Exiguobacterium sp., B. pumilus and B. fusiformis producing extracellular alkaline proteases, amylases and cellulases - a preliminary report - V, Thankamani; M S, Lipin Dev (Research in Biotechnology, 2011)
Garden soil samples collected from Angamali, Kerala, India were screened for potent bacteria capable of synthesizing extracellular hydrolytic enzymes. Four bacteria were obtained in pure culture. The isolates were systematically identified by microscopy, Gram and special staining techniques for capsule and spores, biochemical reactions and phylogeny by molecular techniques like 16 S rRNA ene sequencing followed by Blast analysis. Production of protease, cellulase and amylase were detected by inoculating nutrient agar containing casein/ skim milk agar, carboxy methyl cellulose and soluble starch respectively. Alkalophilic and thermophilic properties were investigated by inoculation and incubation of the isolates on specific nutrient media at pH 7-12 and at a wide range of temperatures 28-30, 37, 50 and 650.C. The isolates were coded VTGP. A-D 30808. All the four expressed significant alkalophilic growth at pH 7-12. With respect to protease activity all except A showed marked protease activity over a high pH range pH 7-12 (A-115, B-1119, C-1500, D-1350 Units / ml of liquid culture supernatant). Both C & D secreted protease as early as 8-12 hours on nutrient agar with 0.1% skim milk forming a clear wide zone of casein hydrolysis. Hence the proteases produced were highly alkalophilic. Amylase activity was marked in all (A-37.38, B-27.58, C-27.92, D-34.82 units per ml culture supernatant). On CMC agar, all the four isolates showed CMCase activity indicated by pale yellow zone of hydrolysis of carboxy methyl cellulose agar when tested with Congo red reagent. A, B and C were strongly positive with minimal visible activity in D. But when tested in CMC broth culture the activities were A-6.71, B-4.30, C-6.56 and D 0.58 units/ ml of culture supernatant). 16S r RNA gene sequencing of isolates A to D showed maximum alignment with Alcaligenes sp., Exiguobacterium sp., Bacillus pumilus and B. fusiformis. The sequences have been deposited in GenBank with Accession numbers HQ 848384, HQ 848385, HQ 848386, and HQ 848387.